AKIS as a Strategic Tool for the Sustainable Management of Natural Resources: Current Trends and Future Research Priori-ties (Journal of Namibian Studies : History Politics Culture, 2023)
The new Common Agricultural Policy of the European Union (EU) (2023-2027) envisages a stronger Agricultural Knowledge and Innovation System (AKIS) as a strategic tool that will unite all relevant actors in a co-creation process to ensure knowledge flows within and across Member States. A significant and increasing body of literature focuses on the strategy and processes of strengthening AKIS. However, there is a relative gap in research related to the role of AKIS as a strategic tool in achieving sus-tainability in the farming sector. The purpose of this paper is to provide an extensive overview of the advancements so far of AKIS across the EU when it comes to facilitating the sustainable management of natural resources (SMNR). The paper builds upon a comprehensive review of relevant literature during the last 15 years covering all 28 EU countries (including the United Kingdom until 2019). We conclude that AKIS architecture in most EU countries lacks a comprehensive structure promoting SMNR. Based on the results we identify countries with relatively high intensity of research and development projects linking AKIS as a strategic tool  to SMNR and where SMNR is better integrated to AKIS. Our results can be of interest to the design of stronger AKIS during the new programming period.